Fabrication of DNA‐based Biosensors Driven by Electrostatic Attractions on Electrodes Modified with Reduced Graphene Oxide and Multi‐walled Carbon Nanotubes. Issue 12 (26th October 2022) - Kumari, Prity; Adeloju, Samuel
Abstract: The use of reduced graphene oxide (rGO) and multi‐walled carbon nanotubes (MWCNTs) has attracted considerable interest for fabrication of chemical sensors and biosensors in recent years. In this study, we report on two ultrasensitive DNA biosensors based on a sensing mechanism driven by the electrostatic attraction of [Ru(NH3 )6 ] 3+ cations on electrode surfaces modified with Au‐MWCNTs and Au‐rGO. A one‐step pot synthesis was used to prepare these nanocomposites for the development of the DNA‐based biosensors. The detection of DNA with the biosensors was based on the electrostatic attraction of [Ru(NH3 )6 ] 3+ cations by the anionic phosphate backbone of DNA. The interfacial changes on the electrode surface upon hybridisation were detected by differential pulse voltammetry (DPV). The high conductivity and high surface to volume ratio properties of the carbon materials enabled significant enhancement of the response for the target DNA detection. The DPV response gave linear concentration ranges (LCRs) of 0.1–10, 000 pM and 1–100 pM with the Au‐MWCNT and Au‐rGO‐based biosensors, respectively. Thus, indicating that the MWCNT‐based biosensor was more sensitive for DNA detection and achieved a wider LCR. Nevertheless, both MWCNT and rGO‐based biosensors exhibited very good discrimination against mismatch sequences. Abstract : The use of a morpholino tag DNA is explored for the development of two ultrasensitive DNA nanobiosensors. The detection of DNA on electrode surfaces modified with Au‐MWCNTs and Au‐rGO was based on the electrostatic attraction of [Ru(NH3 )6 ] 3+ cations by the anionic phosphate backbone of DNA. The nanobiosensors selectively distinguish between matched and mismatched sequences.